REVISTING THE EXACT IDENTITY OF VEDIC ĀRYA-S II: WHO ARE THE DĀSAS AND DASYUS? - B. N. NarahariAchar (Prachi Prajna, 2021)
Yajña is a very basic rite of the Vedic people. Āryas are the ones who perform this rite. It is a collaborative effort between the gods and the humans. Pūrus are not the only āryas, there were several āryan tribes. dāsas and dasyus are evil forces who obstruct the performance of the yajña. Contrary to the opinion of certain scholars, dāsa does not refer to non-pūru tribes and dasyu does not refer to the priestly class among the dāsas.